Cultural Heritage as a Driver of Educational Choices: Evaluating the Role of Bugis Values in the Selection of Islamic Private Schools in Indonesia - Muh. Bachtiar Aziz; Fitriani; Nurhasanah R; Achmad Anwar Abidin; Fajri Dwiyama; Mohamad Toha (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
The decision of parents in Bone, South Sulawesi, to send their children to private Islamic schools is significantly influenced by the integration of religious education and Bugis cultural values, particularly the concept of siri' na pacce. This study aims to examine how Bugis cultural heritage impacts school selection and how private Islamic schools cater to these needs by incorporating programs that reinforce both religious and local values. Using a qualitative approach with a phenomenological design, the research involved in-depth interviews with 15 parents. The results indicate that private Islamic schools are more responsive to parental expectations than public schools, offering a curriculum that blends Bugis religious and cultural education. The study identifies five main factors influencing parents’ decisions: preservation of cultural identity, strengthening religious values, harmonizing modern and traditional education, promoting culture-based character formation, and preparing students for globalization while maintaining cultural roots. Private Islamic schools in Bone have developed educational models that integrate Islamic teachings with local norms (pangngadereng) in response to community needs. This research highlights the importance of cultural heritage in educational decision-making and the role of private institutions in adapting to cultural expectations. The findings offer valuable insights for developing education policies that embrace local wisdom and for creating school management models that respect cultural diversity within Indonesia’s education system.